EFEK MEDIASI MOTIVASI KERJA DALAM POLA HUBUNGAN KOMPENSASI PADA KINERJA KARYAWAN - Siti Almaidah (STIE Atma Bhakti, 2022)
Organizations operating in the public sector are required to improve their performance to provide optimal service to the public. Organizations can strive for work efficiency by improving employee performance. Because of this, organizations need to manage human resources optimally, especially those related to employee performance and the factors that influence it. This study aims to find empirical evidence regarding the mediating effect of work motivation in compensation relationship patterns on employee performance. The samples involved in this study were 105 family planning field officers or called PLKB. Samples were drawn using the total sampling technique. Data analysis techniques used research instrument tests consisting of validity and reliability tests, normality tests, outlier tests, and hypothesis testing. Meanwhile, to find out the significance of the mediating variable, the Sobel test was used. The results of this study are statistically proven that compensation contributes positively and significantly to employee performance mediated by work motivation.